2013
DOI: 10.1371/journal.pone.0057029
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Propagule Pressure, Genetic Diversity and Microsite Availability for Senecio vernalis Invasion

Abstract: Genetic diversity is supposed to support the colonization success of expanding species, in particular in situations where microsite availability is constrained. Addressing the role of genetic diversity in plant invasion experimentally requires its manipulation independent of propagule pressure. To assess the relative importance of these components for the invasion of Senecio vernalis, we created propagule mixtures of four levels of genotype diversity by combining seeds across remote populations, across proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…C or F) tended to perform comparatively poorly in isolation (genotype C also exhibited the lowest persistence in the mixed treatment; Supplementary material Appendix 1 Table A1), and thus overall performance of the species improved when the colonist pool was instead comprised of multiple genotypes. These results are similar to other studies that have indicated that the effect of increasing genetic diversity could depend upon the performance of particular genotypes (Vellend et al 2010, Erfmeier et al 2013, Hovick and Whitney 2019, highlighting how the traits of the genotypes in a small or low diversity population could determine its likelihood of success. If the population is comprised of high-performing genotypes (in the case of our experiment those with a high r), then higher genetic diversity is not necessarily required for success and including other poor-performing genotypes may reduce overall species performance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…C or F) tended to perform comparatively poorly in isolation (genotype C also exhibited the lowest persistence in the mixed treatment; Supplementary material Appendix 1 Table A1), and thus overall performance of the species improved when the colonist pool was instead comprised of multiple genotypes. These results are similar to other studies that have indicated that the effect of increasing genetic diversity could depend upon the performance of particular genotypes (Vellend et al 2010, Erfmeier et al 2013, Hovick and Whitney 2019, highlighting how the traits of the genotypes in a small or low diversity population could determine its likelihood of success. If the population is comprised of high-performing genotypes (in the case of our experiment those with a high r), then higher genetic diversity is not necessarily required for success and including other poor-performing genotypes may reduce overall species performance.…”
Section: Discussionsupporting
confidence: 89%
“…While we know both quantity-and genetic-related mechanisms can be involved in the effect of colonist number on success, there is considerable uncertainty across studies in the separate and relative importance of these mechanisms. For many species, increasing either the quantity or genetic diversity of colonists proves beneficial (Ahlroth et al 2003, Memmott et al 2005, Hufbauer et al 2013, SzƱcs et al 2014, Vahsen et al 2018, but others exhibit no benefits when quantity (Drake et al 2005, Fauvergue et al 2007, Crawford and Whitney 2010, Sinclair and Arnott 2017 or genetic diversity are increased (Hovick et al 2012, Erfmeier et al 2013, Robinson et al 2013. Determining what is causing this variability is key to improving our understanding of how the number of colonists affects colonization success, and for informing practical efforts that focus on controlling the colonization process to promote or prevent establishment and growth.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, non-native species were reduced with Low CWD of 1%-30% coverage, which indicates that even small amounts of CWD can have an immediate positive impact on the plant community. Non-native plants on No CWD plots were likely more abundant there due to bare ground providing microsites for germination, lack of competition (particularly in PMM), and elevated soil temperature which would favor these ruderal type non-native weed species with short life cycles [20,21]. These favorable conditions are reduced with CWD application, which likely leads to a subsequent reduction in non-native species.…”
Section: Discussionmentioning
confidence: 99%
“…) have shown that both the numbers of founders (Erfmeier et al . ; Wootton & Pfister ; SzƱcs et al . ) and their genetic background (Crawford & Whitney ; Hufbauer et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since more individuals typically harbour greater genetic diversity, only experiments in which both demography and genetics are manipulated simultaneously can decouple the relationship and reveal potential interactions between the two. The few studies of this kind (reviewed in Sz} ucs et al 2014) have shown that both the numbers of founders (Erfmeier et al 2013;Wootton & Pfister 2013;Sz} ucs et al 2014) and their genetic background (Crawford & Whitney 2010;Hufbauer et al 2013) can affect establishment success separately, or in combination (Ahlroth et al 2003;Hedge et al 2014) during the first and second generations. Only one study has followed colonising populations multiple generations after founding (Wootton & Pfister 2013), and none has yet tested explicitly how these factors and their interactions might affect colonisation of a novel environment.…”
Section: Introductionmentioning
confidence: 99%